(untitled) (Global Journal of Science Frontier Research, 2016)
The study was conducted to establish the morphological, physical and chemical properties of soils on a toposequence underlain by mica schist in Ife Area, identify the pedogenic processes that produced the soils and establish the taxonomic and fertility capability classes of the soils. The toposequence was delineated into five physiographic units and soil profile pits were established, described and sampled at each unit. The soil samples collected from each of the genetic horizon were subjected to routine analyses following the procedures in methods of soil analysis. Taxonomic and fertility capability classification of the soils were carried out.